Functional analysis of prohibitin in Trypanosoma brucei - Týč, Jiří (Jihočeská univerzita, 2010)
In this study the importance of prohibitin1 and prohibitin2 genes for Trypanosoma brucei was examined. RNA interference showed both of them essential for parasites to survive. Knocking down of these genes resulted in altered morphology of the mitochondrion, changes in membrane potential and shut down of mitochondrial translation. No changes were observed in levels of Reactive Oxygen Species and respiration. Both prohibitines are part of big complex present in the mitochondrion.
Functional analysis of prohibitin in Trypanosoma brucei
Keywords: Trypanosoma; Prohibitin; Knock-down; RNAi; mitochondrion; Trypanosoma; Prohibitin; Knock-down; RNAi; mitochondrion